DAMPAK PANDEMI COVID-19 TERHADAP EKOWISATA DI PROVINSI BANTEN DAN STRATEGI PENGELOLANNYA - Guntur Fernanto; Muhlisin Muhlisin; Jaka Permana (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2023)
Seeing these problems, a strategy is needed that can help overcome problems in the ecotourism management strategy affected by the Covid-19 pandemic in Banten Province. In the context of developing ecotourism into economic growth through the support of job creation and increasing tax revenues, and setting a development strategy in the new adaptation period but by thinking about the sustainability and involvement of local communities, this research was carried out in the Banten Province Region by taking the ecotourism research locus in the Pandeglang Regency and Serang Regency, from July to August 2021, the method used in this study is the SWOT analysis method so that in the decision-making process it can be a reference, the results of the study show that closed tourist attractions and a reduction in the number of visits during the PPKM period affect tourist visits. which in turn affects the income of tourism managers, the chosen ecotourism strategy in dealing with the selected pandemic period is the WT strategy. This defensive strategy (Weakness-Threath) is a tactic to survive by reducing internal weaknesses and avoid threats